Analisa Perbandingan Interpretasi Atas Pemberlakuan Suku Bunga Bank Antara M. Sayyid Thantawi Dan Yusuf Al-Qardhawi - Dwi Umardani (Universitas Muhammadiyah Surabaya, 2022)
Abstract This study is conducted to determine the interpretation of the application of bank interest rate. The method used is a qualitative method with primary and secondary data collected through literature review and then analyzed using a comparative method. After comparing the opinions of the two contemporary muslim intellectuals M. Sayyid Thanthawi and Yusuf Al-Qardhawi on bank interest rate and then analyzing the main arguments of the two, the author can point out that M. Sayyid Thanthawi is of the view that bank interest rate is not the same as riba and is halal while Yusuf Al-Qardhawi is of the view that bank interest rate is the same as riba and is haram. Keywords: Riba, bank interest rate, halal, and haram